Overcoming Multidrug‐Resistant MRSA Using Conventional Aminoglycoside Antibiotics - Tan, Lei (Adv Sci (Weinh), 2020)
Global multidrug‐resistant (MDR) bacteria are spreading rapidly and causing a great threat to human health due to the abuse of antibiotics. Determining how to resensitize MDR bacteria to conventional inefficient antibiotics is of extreme urgency. Here, a low‐temperature photothermal treatment (PTT, 45 °C) is utilized with red phosphorus nanoparticles to resensitize methicillin‐resistant Staphylococcus aureus (MRSA) to conventional aminoglycoside antibiotics. The antibacterial mechanism is studied by the proteomic technique and molecular dynamics (MD) simulation, which proves that the aminoglycoside antibiotics against MRSA can be selectively potentiated by low‐temperature PTT. The catalytic activity of 2‐aminoglycoside phosphotransferase (APH (2″))—a modifying enzyme—is demonstrated to be obviously inhibited via detecting the consumption of adenosine triphosphate (ATP) in the catalytic reaction. It is also found that the active site of aspartic acid (ASP) residues in APH (2″) is thermally unstable from the results of molecular dynamics simulation. Its catalytic ability is inhibited by preventing the deprotonating procedure for the target —OH of gentamycin. The combined therapy also exhibits great biocompatibility and successfully treats MRSA infections in vivo. This low‐temperature PTT strategy has the potential to be an exogenous‐modifying enzyme inhibitor for the treatment of MDR bacterial infection.